2022
DOI: 10.1177/09610006221081895
|View full text |Cite
|
Sign up to set email alerts
|

Information literacy in the legal workplace: Current state of lawyers’ skills in Pakistan

Abstract: This study investigated the current state of information literacy (IL) skills among lawyers practicing at the District Bar Association of Sargodha, Punjab, Pakistan. A cross-sectional survey using a questionnaire was conducted to collect data from 297 lawyers. The questionnaire comprised 20 statements related to information literacy along with certain demographic variables. Each lawyer was personally visited in the assigned chamber by one of the researchers to record responses. Both descriptive (frequencies, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 84 publications
3
7
1
Order By: Relevance
“…This finding is also partially in line with the results of Zhang and Wang (2022) who reported that the investigative journalists recruited from different countries had average levels of information skills and literacy in the era of social media. However, this finding contradicted that of many other relevant studies in Pakistan addressing IL in other professional contexts such as scientists (Anwar, 1981;Naveed, 2022;Naveed and Rafique, 2018), investigation officers (Naveed and Kamran, 2022), lawyers (Naveed and Shah, 2022), teachers (Rafique, 2014;Santos and Oliveira, 2013) and librarians (Ali and Richardson, 2018) as these studies reported that the IL skills of the survey participant were not at the optimum levels.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…This finding is also partially in line with the results of Zhang and Wang (2022) who reported that the investigative journalists recruited from different countries had average levels of information skills and literacy in the era of social media. However, this finding contradicted that of many other relevant studies in Pakistan addressing IL in other professional contexts such as scientists (Anwar, 1981;Naveed, 2022;Naveed and Rafique, 2018), investigation officers (Naveed and Kamran, 2022), lawyers (Naveed and Shah, 2022), teachers (Rafique, 2014;Santos and Oliveira, 2013) and librarians (Ali and Richardson, 2018) as these studies reported that the IL skills of the survey participant were not at the optimum levels.…”
Section: Discussioncontrasting
confidence: 68%
“…Later on, Naveed (2022) and Naveed and Rafique (2018) addressed information literacy among scientists in Pakistan and reported that the scientists were good in basic IL skills and less comfortable with advanced IL skills. The recent studies by Naveed and Shah (2022) and Naveed and Kamran (2022) assessed the IL skills of lawyers and investigation officers respectively and reported that the IL skills of the survey participants were not at optimum level. An inquiry by Sasikala and Kumari (2013) highlighted an increased role of information in the industry and reported the current state of IL initiatives at workplaces in India.…”
Section: Workplace Information Literacy (Wil)mentioning
confidence: 99%
See 1 more Smart Citation
“…The IL value creation is dependent on how well workforce perform in the workplace, particularly in environmental scanning, managing information, and research and development and the quality of information, follow [8]. IL builds the capacity of the workforce in undertaking information-related tasks, making the best information use along with its judicious interpretations and adopting an appropriate information behavior, and making an informed decisions to achieve organization goals [9][10][11]. Therefore, the corporations needed to become information literate to monitor new, unique, and prevailing trends in the market and develop such products which had potential to meet market needs.…”
Section: Introductionmentioning
confidence: 99%
“…With the voluminous growth of information and the realization that the organization must have to deal with it, the information literate workforce is essential to achieve a sustainable competitive advantage. Therefore, IL research in workplace context has not only witnessed growth in the last decade but also gaining a phenomenal momentum [1,2,11]. Of the seminal works, Ref.…”
Section: Introductionmentioning
confidence: 99%